Dominant vs. non-dominant shoulder morphology in volleyball players and associations with shoulder pain and spike speed - Challoumas, D.; Artemiou, A.; Dimitrakakis, G. (Journal of Sports Sciences, 2017)
Abstract: The aims of our study were to compare the dominant (DOM) and non-dominant (NDOM) shoulders of high-level volleyball athletes and identify possible associations of shoulder adaptations with spike speed (SS) and shoulder pathology. A total of 22 male volleyball players from two teams participating in the first division of the Cypriot championship underwent clinical shoulder tests and simple measurements around their shoulder girdle joints bilaterally. SS was measured with the use of a sports speed radar. Compared with the NDOM side, the DOM scapula was more lateralised, the DOM dorsal capsule demonstrated greater laxity, the DOM dorsal muscles stretching ability was compromised, and the DOM pectoralis muscle was more lengthened. Players with present or past DOM shoulder pain demonstrated greater laxity in their DOM dorsal capsule, tightening of their DOM inferior capsule, and lower SS compared with those without shoulder pain. Dorsal capsule measurements bilaterally were significant predictors of SS. None of the shoulder measurements was associated with team roles or infraspinatus atrophy, while scapular lateralisation was more pronounced with increasing years of experience, and scapular antetilting was greater with increasing age. Adaptations of the DOM shoulder may be linked to pathology and performance. We describe simple shoulder measurements that may have the potential to predict chronic shoulder injury and become part of injury prevention programmes. Detailed biomechanical and large prospective studies are warranted to assess the validity of our findings and reach more definitive conclusions.